Obesity, Cardiovascular and Neurodegenerative Diseases: Potential Common Mechanisms - Kuneš, Jaroslav; Hojná, Silvie; Mráziková, Lucia; Montezano, Augusto; Touyz, Rhian M; Maletínská, Lenka (Physiological research, 2023)
The worldwide increase in the incidence of obesity and cardiovascular and neurodegenerative diseases, e.g. Alzheimer's disease, is related to many factors, including an unhealthy lifestyle and aging populations. However, the interconnection between these diseases is not entirely clear, and it is unknown whether common mechanisms underlie these conditions. Moreover, there are currently no fully effective therapies for obesity and neurodegeneration. While there has been extensive research in preclinical models addressing these issues, the experimental findings have not been translated to the clinic. Another challenge relates to the time of onset of individual diseases, which may not be easily identified, since there are no specific indicators or biomarkers that define disease onset. Hence knowing when to commence preventive treatment is unclear. This is especially pertinent in neurodegenerative diseases, where the onset of the disease may be subtle and occur decades before the signs and symptoms manifest. In metabolic and cardiovascular disorders, the risk may occur in-utero, in line with the concept of fetal programming. This review provides a brief overview of the link between obesity, cardiovascular and neurodegenerative diseases and discusses potential common mechanisms including the role of the gut microbiome.
Keywords: Humans; obezita; Alzheimer Disease; Alzheimerova nemoc; neurodegenerativní nemoci; lidé; Obesity; Neurodegenerative Diseases